Catestatin and vasostatin concentrations in healthy dogs. Issue 1 (December 2017) - Srithunyarat, Thanikul; Hagman, Ragnvi; Höglund, Odd; Olsson, Ulf; Stridsberg, Mats; Jitpean, Supranee; Lagerstedt, Anne-Sofie; Pettersson, Ann
Abstract Background The neuroendocrine glycoprotein chromogranin A is a useful biomarker in humans for neuroendocrine tumors and stress. Chromogranin A can be measured in both blood and saliva. The objective of this study was to investigate concentrations of and correlation between the chromogranin A epitopes catestatin and vasostatin in healthy dogs accustomed to the sample collection procedures. Blood and saliva samples were collected from 10 research Beagle dogs twice daily for 5 consecutive days, and from 33 privately-owned blood donor dogs in association with 50 different blood donation occasions. All dogs were familiar with sample collection procedures. During each sampling, stress behavior was scored by the same observer using a visual analog scale (VAS) and serum cortisol concentrations. Catestatin and vasostatin were analyzed using radioimmunoassays for dogs. Results The dogs showed minimal stress behavior during both saliva sampling and blood sampling as monitored by VAS scores and serum cortisol concentrations. Few and insufficient saliva volumes were obtained and therefore only catestatin could be analyzed. Catestatin concentrations differed significantly and did not correlate significantly with vasostatin concentrations (P  < 0.0001). Age, gender, breed, and time of sample collection did not significantly affect concentrations of plasma catestatin, vasostatin, and saliva catestatin. Conclusions The normal ranges of plasma catestatin (0.53–0.98 nmol/l), vasostatin (0.11–1.30 nmol/l), and saliva catestatin (0.31–1.03 nmol/l) concentrations in healthy dogs accustomed to the sampling procedures were determined. Separate interpretation of the different chromogranin A epitopes from either saliva or plasma is recommended.